Posttransplant Lymphoproliferative Disorder in a Patient with Worsening Ascites after Liver Transplantation - Harsh D. Patel; Moises I. Nevah Rubin (Case Reports in Hematology)
Posttransplant lymphoproliferative disorder (PTLD) is a spectrum of diseases that involves abnormal lymphoid and/or plasmacytic proliferation in patients with solid organ or hematopoietic cell transplantation. It is a condition with a low incidence of 3.5–4.3% in liver transplant (LT) recipients. This case involves a 63-year-old male with history of LT for chronic HCV induced cirrhosis who presented with abdominal distension related to worsening ascites. Cytological ascitic fluid analysis revealed EBV (+) malignant cells without a malignant focal point on imaging. Diagnosis of monomorphic PTLD with primary effusion lymphoma-like morphology and immunophenotype was established. This case highlights the complexity in diagnosis, different diagnostic modalities, and rare clinical presentations of PTLD.